Calculation of hemodynamics by the Fick method in pulmonary hypertension associated with congenital heart defects - A. A. Shmalts; T. V. Martynyuk; S. N. Nakonechnikov (Евразийский Кардиологический Журнал)
In December, 2021 at the IXth All-Russian Congress «Pulmonary Hypertension – 2021» the first Eurasian guidelines for the diagnosis and treatment of pulmonary hypertension associated with congenital heart disease (CHD) in adults were approved. In this review, the expert group presents the basic principles of calculating hemodynamics according to Fick for the systemic and pulmonary circulation. The method is indispensable for congenital heart defects. Theoretical and practical aspects of calculating hemodynamics with arteriovenous, venoarterial and bidirectional shunting are considered. The calculation of the cardiac index of each of the circles of blood circulation is performed on the basis of oxygen consumption, the oxygen capacity of the blood and the oxygen arteriovenous difference of each of the circles of blood circulation. Formulas are given for calculating the cardiac index of the systemic and pulmonary circulation, the cardiac index of effective blood flow, arteriovenous and venoarterial shunt, pulmonary and peripheral vascular resistance, as well as the classical table and the LaFarge and Miettinen formula for the calculated oxygen consumption depending on gender, age and heart rate. The review is illustrated with three clinical examples. Calculation of hemodynamics according to Fick should be started after getting acquainted with the anatomy and clinic of congenital heart disease: diagnosis, typical hemodynamic disorders, number and possible direction of shunts, saturation by pulse oximeter on the arms and legs; a purely mechanistic approach that does not take into account the clinical picture can reduce the information content and reliability of the method. The Fick method is somewhat limited by the impossibility of catheterization of the left atrium with an intact interatrial septum. Inaccuracies that are possible when assessing absolute indicators by the indirect Fick method are leveled when calculating their relative values, and the values are identical in reliability to the direct method. The Fick method, due to the obviously high error, is not advisable to use if there is another source of pulmonary blood flow besides the pulmonary artery system, as well as with a low arteriovenous difference in circulatory circles.